Waist-to-Height Ratio Is a Better Anthropometric Index than Waist Circumference and BMI in Predicting Metabolic Syndrome among Obese Mexican Adolescents - Edel Rafael Rodea-Montero; María Lola Evia-Viscarra; Evelia Apolinar-Jiménez (International Journal of Endocrinology)
Objective. To identify the degree of association between anthropometric indices and components of metabolic syndrome (MS) and to determine optimal cut-off points of these indices for predicting MS in obese adolescents. Methods. A cross-sectional study with a sample of (n=110) Mexican obese adolescents grouped by sex and the presence/absence of MS. BMI percentile, waist circumference (WC), and waist-to-height ratio (WHtR) were tested. ROC curves of the anthropometric indices were created to identify whether an index was a significant predictor of MS. Results. BMI percentile, WC, and WHtR were significantly correlated with systolic and diastolic blood pressure. As predictors of MS overall patients, the BMI percentile generated an area under curve (AUC) of 0.651 (P=0.008), cut-off point above the 99th percentile. WC generated an AUC of 0.704 (P<0.001), cut-off point of ≥90 cm. WHtR demonstrated an AUC of 0.652 (P=0.008), cut-off point of 0.60. WHtR ≥0.62 and WHtR ≥0.61 generate AUC of 0.737 (P=0.006) and AUC of 0.717 (P=0.014) for predicting hypertension and insulin resistance, respectively, in females. Conclusion. WHtR is a better tool than WC and BMI for identifying cardiometabolic risk. The overall criterion (WHtR ≥ 0.6) could be appropriate for predicting MS in obese Mexican adolescents.